Rapidly growing non-tuberculosis mycobacterial (NTM) in sputum samples of Iraqi T.B. patients in TB reference lab. in Baghdad - Hamed, Hind; Saleh, Dhuha (Iraqi Journal of Science, 2024)
Non tuberculous mycobacteria (NTM) present in the environment, mainly in water and not transmitted from human to human. The lung is the most common target of NTM infections in human. The symptoms of NTM infection are: fever, weight loss and abdominal pain.114 sputum samples were examined microscopically using Ziehl-Nelsen stain, all were positive. They cultured on Lowenstein-Jensen media.The results of this study indicate presence of 3 (2.6%) of rapidly growing mycobacteria, phenotypically they resemble T.B. bacilli. They were diagnosed by biochemical tests, they were positive for catalase and pyruvate, negative for niacin, nitrate reduction test, sensitive for Thiophene-2-carboxyl acid hydrozide test& resistant for Para nitro Benzoic acid test. Drug susceptibility test showed that two of these isolates were resistant to isoniazid and rifampicin (MDR/multidrug resistance) while one isolate sensitive to all drugs. This study is a part of a subject aiming to estimate MDR-TB in Iraqi patient.